Phytochemical profiling and antioxidant assessment of Cassia auriculata leaves via GC-MS - Ranaware, Abhishek M; Nalawade, Savita P. (Creative Pharma Assent, 2025)
Background: This research aimed to investigate the phytochemical composition, quantify key bioactive compounds such as phenolics and flavonoids, analyze the secondary metabolite profile using GC-MS on methanolic leaf extracts, and evaluate the antioxidant capacity via the DPPH assay. Methodology: The Soxhlet extraction method is employed to obtain crude extracts of Cassia auriculata using solvents including ethanol, methanol, chloroform, and water. These extracts undertook qualitative analysis to detect various bioactive phytochemicals. The total phenolic and flavonoid concentrations were quantified. The methanolic leaf extract underwent phytochemical analysis using a gas chromatography-mass spectrometry (GC-MS) device, following established procedures. The antioxidant capacity of the methanolic leaf extracts was assessed by determining their ability to scavenge free radicals of 2,2-diphenyl-1-picrylhydrazyl. Results and Discussion: Initial phytochemical screening revealed the presence of various secondary metabolite groups. Out of all the solvent extracts assessed, the methanolic extract displayed the highest concentrations of phenolic and flavonoid compounds, measuring 9.48 ± 0.06 mg of Gallic acid equivalents per gram of extract and 6.56 ± 0.03 mg of Quercetin equivalents per gram of extract, respectively. GC-MS analysis of the methanolic extract identified 28 bioactive compounds with known pharmacological significance. Conclusion: The antioxidant activity, evaluated using the DPPH radical scavenging assay, demonstrated that the methanolic extract had the most potent radical scavenging effect among the extracts tested (IC50-48.96 µg/ml). These findings suggest that Cassia auriculata leaves extract is a promising source of natural antioxidants and bioactive compounds, supporting its traditional use in herbal medicine.